Africa RISING-On-Farm Testing and Dissemination of Combination of Technologies in Northern Ghana - International Institute of Tropical Agriculture; Ministry of Food and Agriculture, Government of Ghana; Savanna Agricultural Research Institute (International Food Policy Research Institute, 2016)
Project title: On-Farm Testing and Dissemination of Combination of Technologies. Project abstract: This project was conceived with the goal to evaluate the performance and farmers' preference for early maize varieties through on farm testing and dissemination of combination of technologies. Project website: http://africa-rising.net http://africa-rising.net/where-we-work/west-africa